Psychological treatment of sexual problems. A review of literature published between 2001 and 2010. Presentation of method and preliminary results. Issue 1 (2nd January 2016) - Almås, Elsa; Almås, Cecilie Brøvig
ABSTRACT: While the quality of treatment traditionally has been a reflection of educational diplomas and professional licences, clinicians are now challenged to document treatment methods based on updated research. The American Psychological Association published a report on evidence-based practice in psychology in 2006, where best available research evidence is based on multiple types of research evidence. The report focuses on clinical expertise and patient characteristics, culture and preferences as factors in evidence-based practice in psychology. There has been a call for more randomized and controlled research as basis for evidence for the effect of treatment. The complexity of psychological treatment of sexual problems calls for more varied evidence. A literature search of publications between 2001 and 2010 was done in order to explore what kind of evidence is referred to in the literature. The first results of this search will be presented in this article. One question to be discussed is difficulties related to collecting literature through databases. Additional search methods like snow-balling and manual searches give important additional results, but limit the stringency of the search. Further results will be presented in future publications.